2016
DOI: 10.1371/journal.pone.0164564
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Rheumatoid Arthritis Show Altered Lipoprotein Profiles with Dysfunctional High-Density Lipoproteins that Can Exacerbate Inflammatory and Atherogenic Process

Abstract: ObjectiveIn order to identify putative biomarkers in lipoprotein, we compared lipid and lipoprotein properties between rheumatoid arthritis (RA) patients and control with similar age.MethodsWe analyzed four classes of lipoproteins (VLDL, LDL, HDL2, HDL3) from both male (n = 8, 69±4 year-old) and female (n = 25, 53±7 year-old) rheumatoid arthritis (RA) patients as well as controls with similar age (n = 13).ResultsAlthough RA group showed normal levels of total cholesterol (TC), low-density lipoprotein (LDL)-cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…Structural modification of apoB or apoB-carrying lipoproteins might be an additional regulatory mechanism. For example, LDL from patients with RA is more unstable; it is susceptible to oxidation and already oxidised in patients with RA 15. Indeed, oxLDL, which is enriched in RA, can induce a greater inflammatory response than naïve LDL,15 16 which is supported by our observation of a stronger interaction of oxLDL than native LDL with ENO1 (online supplementary figure 2).…”
Section: Discussionmentioning
confidence: 52%
“…Structural modification of apoB or apoB-carrying lipoproteins might be an additional regulatory mechanism. For example, LDL from patients with RA is more unstable; it is susceptible to oxidation and already oxidised in patients with RA 15. Indeed, oxLDL, which is enriched in RA, can induce a greater inflammatory response than naïve LDL,15 16 which is supported by our observation of a stronger interaction of oxLDL than native LDL with ENO1 (online supplementary figure 2).…”
Section: Discussionmentioning
confidence: 52%
“…Changes to lipid composition in rheumatoid arthritis are not limited to HDL. LDL from rheumatoid arthritis patients had higher levels of glycated end products and was more oxidized than LDL from controls 78. In vitro, LDL from rheumatoid arthritis patients underwent enhanced phagocytosis by macrophages, had higher fatty acid accumulation, and induced approximately threefold greater oxidation.…”
Section: Mechanisms Linking Rheumatoid Arthritis and Cardiovascular Dmentioning
confidence: 86%
“…HDL cholesterol efflux capacity, that is, the ability to export HDL from immune cells, is damaged in patients with RA. In a previous study, this ability was reported to be related to cardiovascular function . These lipoprotein‐related dysfunctions in patients with RA might be associated with the high incidence of cardiovascular events reported in such patients .…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study, this ability was reported to be related to cardiovascular function . These lipoprotein‐related dysfunctions in patients with RA might be associated with the high incidence of cardiovascular events reported in such patients . Functional analysis of process networks revealed the differentially expressed proteins to be most strongly associated with blood coagulation, which is activated by coagulation factors that are, in turn, induced by the immune response.…”
Section: Discussionmentioning
confidence: 89%